Considerations in Preparative Regimen Selection to Minimize Rejection in Pediatric Hematopoietic Transplantation in Non-Malignant Diseases - Hayashi, Robert J. (Frontiers in Immunology, 2020)
The variables that influence the selection of a preparative regimen for a pediatric hematopoietic stem cell transplant procedure encompasses many issues. When one considers this procedure for non-malignant diseases, elements developed to reduce malignant tumor burden may be unnecessary. The primary goal becomes engraftment with the establishment of normal hematopoiesis and a normal immune system. Overcoming rejection becomes the priority, but pursuit of this goal cannot neglect organ toxicity, or post-transplant morbidity such as life threatening infections. With the improvements in supportive care and the expansion of viable donor sources, we have reached a stage where hematopoietic stem cell transplantation can be considered for virtually any patient with a hematopoietic based disease. Advancing preparative regiments that minimize rejection and transplant related toxicity will thus dictate whether this medical technology is fully utilized. This mini-review will provide an overview of the origins of conditioning regimens for transplantation and how agents and techniques have evolved to make hematopoietic stem cell transplantation a viable option for children with non-malignant diseases of the hematopoietic system. We will summarize the current state of this facet of the transplant procedure and describe the considerations that come into play in selecting a particular preparative regimen. Such a decision ultimately tailors the treatment to the primary disease condition and to patient specific variables that will ideally achieve an optimal outcome. Finally we will project forward where advances are needed to overcome the persistent engraftment obstacles that currently limit the utilization of transplantation for haematopoietic based diseases in children.